Pengaruh Metode Bentuk Latihan Drill Terhadap Peningkatan Keterampilan Teknik Dasar Dribbling - Ari Farhan Rizqullah, Muhammad; Falaahudin, Ardhika (Jurnal Muara Olahraga, 2025)
One of the weaknesses found in students participating in extracurricular futsal at Persatuan Bangsa High School is in basic dribbling techniques. Students participating in extracurricular futsal have weaknesses in the technique of carrying the ball or what is commonly known as the dribbling technique. Therefore, it is necessary to test a form of training method to be able to provide changes in the form of methods that are feasible to use in the basic dribbling techniques of futsal extracurricular participants. This research has the aim of making efforts to improve the dribbling achievements of extracurricular participant students by using the drill training method. This research method uses an experimental method using the entire population of fifteen people. The research was conducted in ten meetings. The results of this study indicate that from the process carried out before and after being given treatment there is an increase. From the results of the t-test that has been carried out, there is an increase between the pretest and posttest results, the t-count value is 5.850 with a degree of freedom (df) of 14 and a significance value (Sig.2 tailed) of 0.000 which is smaller than 0.005. So from these results it can be seen that the process of applying the drill method has an influence in efforts to improve the basic dribbling technique skills of students participating in the futsal extracurricular of Kesatuan Bangsa High School.